Effects of superoxide radical on photosynthesis and K+ and redox homeostasis in quinoa and spinach - Tanveer, Mohsin (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 The Authors. Published by Elsevier Masson SAS.. All rights reserved.